China-Pakistan Economic Corridor: Cooperate Investment Development And Economic Modernization Encouragement - Hussain, Sarfraz; Rafiq, Muhammad; Quddus, Abdul; Ahmad, Nisar; Pham, Tien Phat (The journal of contemporary issues in business and government, 2021)
Although international business and trade cooperation is regarded as a hallmark of the 21st century, the current liberal consensus on economic globalisation has been challenged by new events in Brexit through President Trump 's approach and pro-Trump- Multilateral business trade. This paper will argue that, on the alternative, the CPEC is China's scenarios and Pakistan's latest effort to lift the young generation of international trade, as the one Belt and one Road was suggested by China's economic corridor as a route to growth, whereas the CPEC would be even more valid of ignorance-bringing isolation. It's a game-changer with Pakistan, as that is a forum for economic integration. The CPEC will also flourish in China and Pakistan, but it will have such a positive effect on Iran, Afghanistan , India, the Central Asian Republic, and the region. Foreign business can be fostered by strengthening regional ties as opposed to anti-localization movements.